On Best Proximity Points of Generalized Almost-F-Contraction Mappings - Hamlbarani Haghi, Robab; Salamatbakhsh, Mahdi (IndoMS, 2019)
We provide some results about best proximity points of generalized almost-F-contraction mappings in metric spaces which generalize and extend recentÂ fixed point theorems. Also, we give an example to illustrateÂ our main result.